2019
DOI: 10.1080/17435390.2019.1597203
|View full text |Cite
|
Sign up to set email alerts
|

Vial sonication and ultrasonic immersion probe sonication to generate stable dispersions of multiwall carbon nanotubes for physico-chemical characterization and biological testing

Abstract: 2019) Vial sonication and ultrasonic immersion probe sonication to generate stable dispersions of multiwall carbon nanotubes for physico-chemical characterization and biological testing,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…There are two methods of sonication: tip and bath. Both have a negative effect on CNTs, but the destructive impact of tip sonication is greater, because sound energy is concentrated [32,39,40]. Arnold and co-workers [31] demonstrated that tip sonication time also affects the average length of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…There are two methods of sonication: tip and bath. Both have a negative effect on CNTs, but the destructive impact of tip sonication is greater, because sound energy is concentrated [32,39,40]. Arnold and co-workers [31] demonstrated that tip sonication time also affects the average length of CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the synthesized nanotubes were linear, the perceived defects in the images were due to the ultrasonication procedure. 21 From Figure 3 a, it can be said that the nanotubes have undergone a base growth mechanism and nickel is present within the nanotube. Because the sample was thermally purified, the black particles in the tubes are nickel, as shown in Figure 3 b,c.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their potential usefulness, biomedical applications involving MWCNTs have been limited due to a lack of methods for dispersion and characterization (Rio‐Echevarria, Ponti, Urban, & Gilliland, 2019). The optimal combination of biosurfactants and ultrasonication to overcome the strong van der Waals force (Zhbanov, Pogorelov, & Chang, 2010) as shown here provides well‐dispersed and stabilized MWCNTs in cell culture systems (Figure 1).…”
Section: Discussionmentioning
confidence: 99%